2015
DOI: 10.1557/jmr.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Production of aluminum nitride from aluminum metal using molten fluoride

Abstract: The production of aluminum nitride (AlN) from aluminum metal was investigated in this study. The nitridation of Al (in rod, powder, and thin-plate forms) was facilitated by dissolving the Al 2 O 3 thin films formed on the Al samples with a molten fluoride mixture (KF-45 mol% AlF 3 , KF, or LiF-50 mol% KF). AlN was formed when NH 3 gas was supplied to the Al sample (in both solid and liquid forms) wetted by molten fluoride mixture. The lowest temperature at which AlN was successfully produced was 773 K. No AlN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Because of its simplicity, cost‐effectiveness and lack of toxicity, direct nitridation is one of the primary processes commercially used to manufacture AlN powder. Although various AlN products such as AlN whisker, powder and nanowire have been extensively studied using the direct nitridation method, to the best of our knowledge, little research on the preparation of AlN : Eu 2+ phosphor has been reported. Here, we attempt to synthesize Eu 2+ ‐doped AlN phosphors using the direct nitridation method; the influence of nitridation reaction temperature, post‐heat treatment and Eu 2+ concentration on the photoluminescence of phosphors is also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its simplicity, cost‐effectiveness and lack of toxicity, direct nitridation is one of the primary processes commercially used to manufacture AlN powder. Although various AlN products such as AlN whisker, powder and nanowire have been extensively studied using the direct nitridation method, to the best of our knowledge, little research on the preparation of AlN : Eu 2+ phosphor has been reported. Here, we attempt to synthesize Eu 2+ ‐doped AlN phosphors using the direct nitridation method; the influence of nitridation reaction temperature, post‐heat treatment and Eu 2+ concentration on the photoluminescence of phosphors is also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, P. Wu et al reported the AlN growth method using vaporized Al and nitrogen gas as source materials 10,11) . Some groups fabricated AlN by nitridation of metallic Al [12][13][14] . These techniques are simple, however, fabrication of high quality AlN bulk crystal have not been reported.…”
Section: Introductionmentioning
confidence: 99%